Disparate healthcare experiences of people living with overweight or obesity in England. (November 2021) - Flint, Stuart W.; Leaver, Meghan; Griffiths, Alex; Kaykanloo, Mohammad
Abstract: Background: Ensuring that patients have high quality, equitable experiences in healthcare is a high priority in the UK. As such, identifying and addressing areas where patient experiences are unsatisfactory and inequitable is of high priority, and has been included as part of the National Health Service (NHS) England equity objectives. Methods: The healthcare experiences of people who identified as living with overweight or obesity were gathered from freely available websites using the Patient Experience Platform (PEP). PEP was used to gather and analyse all comments from NHS UK, Google, Facebook and Twitter that related to care experiences of people who identified as living with overweight or obesity across all NHS Acute and Specialist Trusts and all general practitioners (GPs) in England from 01/01/2018 to 31/12/2020. These healthcare experiences were analysed to provide care quality metrics, a comparison of care across regions of England, and to explore associations between behavioural clusters of personality attributes, values and sentiment with care quality metrics. Findings: Perceptions of the quality of care were significantly lower for people who identified as living with overweight or obesity compared to people who didn't identify as living with overweight or obesity across all regions for 'Effective Treatment' and 'Emotional Support'. The perceived quality of care metrics can be predicted by the behavioral clusters, where for instance, the experiences of people who identified as living with overweight or obesity in the negative behavioral cluster have a lower overall perceived quality of care score. Themes arising from the data also highlighted that barriers quality care experienced by people who identified as living with obesity include the speed of access, effective treatment, and emotional support, with stigmatising healthcare experiences are reported. Interpretation: The findings of this study provide insights into the experiences reported via freely available websites, of people who self-identified as living with overweight or obesity in healthcare in England. These insights demonstrate that the perceived quality of care was lower for people who identified as living with overweight or obesity compared to the general population, and that there is regional variation in care quality. The study has also shown that patient experiences differ based on personality attributes, values and sentiment, highlighting the need for patient-centred care and personalised approaches. These findings hold important considerations for healthcare and policy makers aiming to address healthcare inequity. Funding: Novo Nordisk.